AVALIAÇÃO DO STATUS TAXONÔMICO DE POPULAÇÕES RECONHECIDAS COMO Scinax nebulosus (Spix, 1824) e Scinax constrictus (Lima, Bastos & Giaretta, 2004) (Anura, Hylidae) ATRAVÉS DE FERRAMENTAS MOLECULARES - FREITAS, Tatiana Maria Barreto de (2020)
The genus Scinax Wagler, 1830, belonging to the subfamily Scinaxinae, family Hylidae, is represented by 126 species that occupy areas from Mexico, Argentina and Uruguay, including Trinidad, Tobago and Santa Lucia. Resulting from high morphological conservation and the continuous discovery of new non-originated species, the genus is currently considered a taxonomic problem. A species of Scinax constrictus was found as a distinct species from Scinax nebulosus, however without much morphological evidence. Thus, we investigated the taxonomic status of populations identified as Scinax nebulosus and Scinax constrictus, through the phylogenetic analysis of the genus Scinax. Phylogenetic analysis can show us that Scinax remains with its monophyletic characteristic maintained in all analyzed markers and in all analyzes. The genetic validity of S. constrictus and S. nebulosus was also recovered with a high support value. The genetic distances obtained in the three markers indicate that S. constrictus and S. nebulosus are distinct species. Molecular analyzes helped to differentiate populations diagnosed as S. constrictus and S. nebulosus, despite the morphological similarities of both species. Furthermore, we can suggest, through genetic divergence analyzes, that S. nebulosus may present itself as a group of cryptic species due to the genetic characteristics found. The existence of a mosaic of heterogeneous habitats may explain the genetic divergence found, which justifies the existence of cryptic species in this group.